KEBIJAKAN PENANGANAN ABRASI PANTAI DALAM PENYELAMATAN RUANG PANTAI - Perdani, Agung Sandi; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This article examines coastal erosion management policies in Demak Regency, Central Java, one of the most severely affected regions by coastal abrasion in Indonesia. Coastal erosion, driven by both natural factors and human activities, threatens the sustainability of coastal ecosystems as well as the social and economic livelihoods of local communities. Using a Systematic Literature Review (SLR) approach, this study analyzes various policies implemented, ranging from hard infrastructure development to ecosystem-based approaches such as mangrove rehabilitation. The findings reveal that although some policies have shown effectiveness, challenges such as weak inter-agency coordination, limited funding, and low community participation continue to hinder optimal implementation. This article highlights the importance of integrated and sustainable policies, as well as the need for cross-sectoral collaboration to protect coastal spaces and support the welfare of coastal communities. The findings are expected to serve as a reference for policymakers in formulating more effective strategies to address the issue of coastal erosion.